Strategi Komunikasi Takmir dalam Memakmurkan Masjid Jogokariyan Yogyakarta (Communication Strategy of the Mosque Management for Prosperity of Jogokariyan Mosque Yogyakarta) - Atik Nurfatmawati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The magnificent mosque is not necessarily offset the spirit of the prosperity of the mosque. This is different from the Jogokariyan Mosque in Yogyakarta, in addition to congregational prayers it is also a center of social activities. The purpose of this study was to analyze the takmir communication strategy to prosper the Jogokariyan Mosque. This study uses interpersonal communication theory with a descriptive qualitative approach. The informants of this study were four people from the Jogokariyan Mosque. The results of this study are the personal approach strategy is one of the keys to success in building the communication process. Mosque takmir communication with the surrounding community, worshipers, and mosque visitors is carried out persuasively. Takmir Masjid also often holds social activities with the community, both Muslim and non-Muslim. Efforts to make the mosque prosperous through a personal approach, through hobbies that are favored by residents who have not yet prayed. Besides, the mosque takmir seeks to maintain the comfort of guests whether worshiping or just stopping by.